Evolutionary analysis of iron (Fe) acquisition system in Marchantia polymorpha. Issue 2 (7th March 2016) - Lo, Jing‐Chi; Tsednee, Munkhtsetseg; Lo, Ying‐Chu; Yang, Shun‐Chung; Hu, Jer‐Ming; Ishizaki, Kimitsune; Kohchi, Takayuki; Lee, Der‐Chuen; Yeh, Kuo‐Chen
Summary: To acquire appropriate iron (Fe), vascular plants have developed two unique strategies, the reduction‐based strategy I of nongraminaceous plants for Fe 2+ and the chelation‐based strategy II of graminaceous plants for Fe 3+ . However, the mechanism of Fe uptake in bryophytes, the earliest diverging branch of land plants and dominant in gametophyte generation is less clear. Fe isotope fractionation analysis demonstrated that the liverwort Marchantia polymorpha uses reduction‐based Fe acquisition. Enhanced activities of ferric chelate reductase and proton ATPase were detected under Fe‐deficient conditions. However, M. polymorpha did not show mugineic acid family phytosiderophores, the key components of strategy II, or the precursor nicotianamine. Five ZIP (ZRT/IRT‐like protein) homologs were identified and speculated to be involved in Fe uptake in M. polymorpha . MpZIP3 knockdown conferred reduced growth under Fe‐deficient conditions, and MpZIP3 overexpression increased Fe content under excess Fe. Thus, a nonvascular liverwort, M. polymorpha, uses strategy I for Fe acquisition. This system may have been acquired in the common ancestor of land plants and coopted from the gametophyte to sporophyte generation in the evolution of land plants.